Modeling, simulations, and optimization of smooth muscle cell tissue engineering for the production of vascular grafts. Issue 6 (23rd February 2019) - Elsayed, Yahya; Lekakou, Constantina; Tomlins, Paul
Abstract: The paper presents a transient, continuum, two‐phase model of the tissue engineering in fibrous scaffolds, including transport equations for the flowing culture medium, nutrient and cell concentration with transverse and in‐plane diffusion and cell migration, a novel feature of local in‐plane transport across a phenomenological pore and innovative layer‐by‐layer cell filling approach. The model is successfully validated for the smooth muscle cell tissue engineering of a vascular graft using crosslinked, electrospun gelatin fiber scaffolds for both static and dynamic cell culture, the latter in a dynamic bioreactor with a rotating shaft on which the tubular scaffold is attached. Parametric studies evaluate the impact of the scaffold microstructure, cell dynamics, oxygen transport, and static or dynamic conditions on the rate and extent of cell proliferation and depth of oxygen accessibility. An optimized scaffold of 75% dry porosity is proposed that can be tissue engineered into a viable and still fully oxygenated graft of the tunica media of the coronary artery within 2 days in the dynamic bioreactor. Such scaffold also matches the mechanical properties of the tunica media of the human coronary artery and the suture retention strength of a saphenous vein, often used as a coronary artery graft. Abstract : The paper presents a transient, continuum, two‐phase model of the tissue engineering in fibrous scaffolds, including transport equations for the flowing culture medium, nutrient and cell concentration with transverse and in‐plane diffusion and cell migration, a novel feature of local in‐plane transport across a phenomenological pore and innovative layer‐by‐layer cell filling approach.